The Generation and Characterization of the Nrl-/-;Ccdc136+/- Mouse Line to Investigate Cone Photoreceptor Transplantation in Adult Mouse Retinas - Smiley, Sheila (Université d'Ottawa / University of Ottawa, 2014)
Human vision is heavily dependent on cone photoreceptor function and irreversible loss of these cells, caused by retinal degenerative diseases, results in deterioration of central, high acuity vision. Here, I characterized coiled-coil domain containing 136 (Ccdc136) as a cone marker. Ccdc136-/- mice were generated and examined using immunohistochemical and electrophysiological analyses. To investigate cone transplantation, the mice were crossed onto a cone-only neural retina leucine zipper knockout (Nrl-/-) background generating Nrl-/-;Ccdc136+/- donor mice. Ccdc136-/- mice expressed GFP in cone but not rod photoreceptors. Nrl-/-;Ccdc136+/- donor mice had an enriched population of GFP+ cones and showed enhanced cone function, identical to Nrl- /- mice. After transplantation, Nrl-/-;Ccdc136+/- cells migrated successfully into adult recipient retinas. Morphology of integrated cells improved with younger donor age with some integrated cells expressing cone markers. In conclusion, the Nrl-/-;Ccdc136+/- mouse is an appropriate strain to investigate cone photoreceptor transplantation. Future studies aim to improve integration rates to assess vision rescue in degenerated retinas.